THE USE OF MODERN TECHNOLOGIES IN FOREIGN LANGUAGE LESSONS - Ismatov Umidjon Ibodullo o’g’li (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotatsiya: The article explores the use of modern technologies in foreign language lessons, emphasizing their role in enhancing the educational process. By integrating tools such as interactive applications, online resources, and virtual reality, immersive language learning environments can be created for students. This study examines the effectiveness of these technologies, reviews pedagogical methods, and provides recommendations for their optimal implementation.